Analisis Perbandingan Pendekatan Plugged-in dan Unplugged dalam Pengembangan Kemampuan Computational Thinking pada Anak Usia Dini: Tinjauan Sistematis Literature Review - Fajriyah, Lathifatul; Rizqiyani, Revina; Fadilatul Fitria (Universitas Islam Tribakti Lirboyo Kediri, 2022)
The purpose of this study is to find out more about computational thinking learning using plugged and un-plugged. The research method used in this study is a systematic literature review with the aim of detecting and then reviewing relevant research studies published from 2019-2024. It was found that 28 scientific articles had met the inclusion criteria for analysis and would then be analyzed based on their methodology and findings. The results of the study found that computational thinking learning with a plugged and un-plugged approach can be applied to early childhood. The plugged approach aims to make concepts easy to understand for students which can increase their motivation in learning, while the unplugged approach can be used if there are limitations in technological tools.